Positioning Six Sigma within the quality management agenda: a conceptual framework. (1st January 2011) - Rajamanoharan, Indra Devi; Collier, Paul; Wright, Brian
This paper traces and charts the evolution of quality management, from inspection to the present day innovative concepts of Six Sigma (SS) process improvements. The reason for exploring the evolution of quality management is to develop a framework that places SS in its context – within the quality management agenda. Consistent with other studies, the proposed framework uses a timeline structure to analyse the literature on quality management developments leading to the development of the SS quality approach. The review of the literature shows that like TQM, SS placed within the strategic quality management era, portrays a whole systems view for quality management, but goes a step further than TQM approach to link performance improvement activities to bottom-line performance. Further, SS under the influence of strategic quality management approach is closely linked to process management, customer orientation and the company's strategic objectives. It is also noted that SS's innovative approach, from a functional to a process centric approach, has shifted the quality responsibility from the quality control department to individual process owners who are exclusive members of an SS team structure.